The development of early childhood sex education materials for early childhood education (ECE) teachers - Budi Astuti; Sugiyatno Sugiyatno; Siti Aminah (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2017)
The objective of this research was to create early childhood sex education materials for Early Childhood Education Teachers. The research was initiated by conducting need assessment in the form of identification of the needs of sex education materials that appropriate for early childhood and the role of teachers and parents in the sex education. The subjects were chosen by using the purposive technique. The subjects of this study were 28 Early Childhood Education teachers in Sleman Regency. The data collection in this research was using a questionnaire. The data analysis technique was using quantitative descriptive techniques. The results of the research provided a description that the materials about the skills to protect themselves from sexual violence is the most needed matter of Early Childhood Education teachers. Further, respectively according to the level of need, the material that needs to be included in a Early Childhood Sex Education is the introduction of the gender, the introduction of self-identity, the relationship of men and women and ways to maintain the health,  and the introduction of reproductive organs and functions. Materials product is expected to be a guideline and reference in providing early sex education.